Stated preferences and actual choices in german health insurance - Anna Werbeck (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Hypothetical bias is the discrepancy between stated preferences and actual choices. As such, it is one of the key issues regarding the use of hypothetical survey methods and therefore highly relevant for economists in understanding human behavior and refining policy interventions. Hypothetical survey methods are often used to inform our view on decision making in health and financial settings. However, there is limited understanding of the extent and underlying factors of hypothetical bias within the context of health insurance. This study contributes to this understanding and explores the extent of hypothetical bias and its correlation with personality traits and behavioral patterns in a health insurance setting. Using large-scale survey data in tandem with detailed information on health plans, I show that the majority of enrollees overestimate their willingness to switch health plans when facing a price increase: 64% show hypothetical bias. Especially conscientious, impulsive or negative reciprocal individuals are prone to hypothetical bias. In contrast, internal locus of control correlates with consistent preferences. These findings can help refine mitigation strategies and assess the reliability of stated preferences. – – Der hypothetische Bias ist die Diskrepanz zwischen angegebenen Präferenzen und tatsächlichen Entscheidungen. Als solcher ist er eines der zentralen Probleme bei der Verwendung von Umfragedaten und daher für Ökonomen von hoher Relevanz, um menschliches Verhalten zu verstehen und politische Interventionen zu verfeinern. Umfragen werden häufig genutzt, um Präferenzen im Gesundheits- und Finanzkontext abzufragen. Kentnisse über das Ausmaß und die zugrunde liegenden Faktoren von hypothetischem Bias grade im Kontext von Krankenversicherungen sind derzeit jedoch noch begrenzt. Diese Studie setzt hier an und untersucht das Ausmaß des hypothetischen Bias und dessen Korrelation mit Persönlichkeitsmerkmalen und Verhaltensmustern im Kontext einer Krankenversicherungsreform. Die Studie zeigt, dass die Mehrheit der Krankenversicherten ihre Bereitschaft, bei einer Preiserhöhung den Versicherungsplan zu wechseln, überschätzt: 64% zeigen hypothetischen Bias. Besonders gewissenhafte, impulsive oder negativ reziproke Personen neigen eher dazu in ihren Handlungen von den angegebenen Präferenzen abzuweichen. Personen mit hoher interner Kontrollüberzeugung neigen eher zu konsistenten Präferenzen.
Keywords: D91; G40; I13; 330; Behavioral; hypothetical bias; finance; health insurance